Evaluasi Usability Aplikasi Dompet Digital Memakai Metode System Usability Scale pada Mahasiswa Penghuni Indekos - Fitri, Tasya Aulia; Agnia Sri Ayu; Kamila Rosa Br. Bukit; Sazwani Ardhia Sahira; M. Khalil Gibran (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
Digital financial service developments have also increased the use of digital wallet applications among university students, especially boarding house residents who have relatively high daily transaction needs. This study was conducted to examine the ease of use level of digital wallet applications by applying the System Usability Scale (SUS) approach. The research data were obtained through questionnaire distribution to 20 respondents who actively use digital wallet applications. Furthermore, the collected data were processed to determine the system usability level based on the SUS score obtained. The results showed an average SUS score of 74, which falls into the acceptable category with grade B and adjective rating Good. Although the application has been able to provide a fairly positive user experience, several aspects still require improvement, particularly in navigation arrangement and interface consistency.